Tuberculosis en el mundo laboral colombiano 1934-1946 - Oscar Gallo Vélez; Jorge Márquez Valderrama (Nuevo mundo - Mundos Nuevos, 2016)
The historiography on tuberculosis in Colombia does not include studies covering the connection between this illness and the working world. When analysing this issue, we are able to appreciate its richness based on several facts : an increase in tuberculosis occurrences across the twentieth century ; the survival of a segregationist imaginary of the tuberculous ; the debate around classifying tuberculosis as an occupational disease. We are aiming to understand the links between the reality of tuberculosis and workers in the Colombian context, finding that both facts cannot be separated from the history of occupational diseases, occupational medicine, and the emergence of social security. The tuberculous worker has been the junction point of a thread of events, debates, and local and global processes marking the transition from a notion of tuberculosis as a hindrance for work towards the realization of work as a potential pathogen in tuberculosis. Such a transition occurred in the context of health economics including tuberculosis in the risk rationale and in the assessment of occupational disease, within the bounds of debates involving patients, lawmakers, businessmen, occupational physicians and the State.